Synthesis of ethyl oleate by esterification in a solvent-free system using lipase immobilized on PDMS-modified nonwoven viscose fabrics. Issue 11 (November 2015) - Li, Weina; Shen, Huaqing; Ma, Miaomiao; Liu, Luo; Cui, Caixia; Chen, Biqiang; Fan, Daidi; Tan, Tianwei
Graphical abstract: Iterative batches with reuse of the immobilized lipase and stepwise addition of ethanol. Highlights: The hydrophobic immobilized lipase exhibited less affinity with oleic acid. The degree of ethanol inhibition for the hydrophobic immobilized lipase was reduced. Detachment of lipase affects catalyst function less than increase in water content. The immobilized lipase can be reused for 10 batches in BSTR. Abstract: A lipase from the yeast Yarrowia lipolytica was immobilized on a PDMS-modified nonwoven viscose fabric and used in the synthesis of ethyl oleate. The efficiency of immobilization improved to 75.2% when the concentrated lipase slurry (180 mg mL −1 ) was used as the source of lipase. When compared with the original immobilized lipase, the lipase immobilized on the PDMS-modified fabric exhibited more stable catalytic activity over 35 batches; exhibited a 20-fold lower affinity for oleic acid, a 42-fold less ethanol-induced inhibition; could be reused in 10 iterative 5L batch stirred tank reactor processes. When compared to that of free lipase, the pH stability range of immobilized lipase was narrower (pH 6–7 vs pH 5–8); the optimum reaction temperature was higher (40 °C vs 37 °C); and the thermally more stable (70% vs 5% of activity was retained after pre-incubation for 4 h at 45 °C). The variation in the activity exhibited in an organic solvent could be correlated to the log P. Catalytic efficiency was ∼13-fold lower upon excessive lipase immobilization. XPS/ATR-FTIR confirmed the introduction of PDMS onto lipase-immobilized viscose. The simple enzyme immobilization method could potentially be useful for the production of ethyl oleate at an industrial scale.